Acoustic radiation force impulse elastography: comparison and combination with other noninvasive tests for the diagnosis of compensated liver cirrhosis - Pfeifer, Lukas; Adler, Werner; Zopf, Steffen; Wildner, Dane; Görtz, Rüdiger; Schellhaas, Barbara; Neurath, Markus; Strobel, Deike; Siebler, Jürgen (European Journal of Gastroenterology & Hepatology, 2017)
BACKGROUND AND AIMS: The aim of this study was to compare acoustic radiation force impulse (ARFI) elastography with other noninvasive tests and to develop a new score for the assessment of liver fibrosis/cirrhosis. MATERIALS AND METHODS: B-mode ultrasound (including high-frequency liver surface evaluation), routine blood tests, ARFI quantification, and mini-laparoscopic liver evaluation were obtained in compensated patients scheduled for mini-laparoscopic biopsy. Our new cirrhosis score (CS) for the assessment of liver cirrhosis, based on a linear combination of ARFI, platelet (PLT), liver surface, and prothrombin index (PI), was calculated by linear discriminant analysis. Its performance was compared with ARFI-elastography, APRI, FIB-4, alanine aminotransferase (ALT)/aspartate aminotransferase (AST)-ratio, PLT, and PI. For the diagnosis of cirrhosis, a combined gold standard (cirrhosis at histology and/or at macroscopic liver evaluation) was used. RESULTS: In total, 171 patients, of whom 38 had compensated cirrhosis, were included. The CS was significantly better for the diagnosis of cirrhosis compared with ARFI (P=0.028), APRI (P=0.012), PLTs (P=0.013), PI (P=0.025), and ALT/AST ratio (P=0.001), but not the FIB-4 score (P=0.207), with an area under the receiver operating characteristic curve of 0.92 [95% confidence interval (CI): 0.87-0.97], 0.86 (95% CI:0.79-0.93), 0.80 (95% CI: 0.72-0.87), 0.79 (95% CI: 0.7-0.87), 0.81 (95% CI: 0.73-0.89), 0.72 (95% CI:0.64-0.81), and 0.86 (95% CI: 0.8-0.93), respectively. Sensitivity, specificity, positive predictive value, and negative predictive value for CS were 87%, 86%, 63%, and 96%, respectively. The FIB-4 score was significantly superior to the APRI score (P=0.041) and the ALT/AST ratio (P=0.011), with no significant difference from ARFI elastography (P=0.88) for the diagnosis of cirrhosis. CONCLUSION: Combining ARFI elastography with other noninvasive tests that are used routinely in the workup of patients with suspected liver disease can improve diagnostic accuracy for compensated liver cirrhosis as compared with ARFI elastography alone. The FIB-4 score showed an overall comparable diagnostic accuracy to ARFI-elastography for compensated cirrhosis.
EVALuna2:33816